Lateral sellar angiolipomas: a therapeutic challenge. Our experience on two cases and review of the literature. (June 2013) - Rotondo, M.; D'Avanzo, R.; Natale, M.; Oliva, G.; Scuotto, A.
Abstract Angiolipomas are rare benign mesenchymal tumours, most commonly found in the subcutaneous tissue of the extremities. These neoplasms are rarely located in the central nervous system (CNS), with spinal localization being the most common in this group. Intracranial location is extremely infrequent, and only ten cases have been described in the sellar region. We report on two more patients with skull-base (intracranial) angiolipomas, the former presented with a long history of headache and the latter complained diplopia. Both patients were postoperatively verified as angiolipoma. Neuroimaging studies and peroperative features are presented and the role of microsurgery is discussed. On the basis of these tumours' characteristics, the management strategy of choice usually does not consist on surgical total removal, often a partial excision could be satisfying to improve the patient symptomatology. Nowadays, Gamma Knife surgery is standing out as an effective, additional and/or alternative, treatment modality.